KEMAMPUAN MENULIS SURAT PRIBADI SISWA KELAS VIII MTs AS-SYAFI’IYYAH DESA AIR PANAS KECAMATAN PENDALIAN IV KOTO - Novy Setiowati; Abdul Razak; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study examines the ability to write personal letters of class VIII students MTs As-Syafi'iyyah Air Panas Village Pendalian IV Koto Districts. The purpose of this research is to describe the high level of personal letter writing ability of grade VIII students of MTs As-Syafi'iyyah Air Panas Village Pendalian IV Koto Districts and describe the difference of personal letter writing ability according to sample group. This study has a population of 49 and a sample of 44. To know the high-low ability of writing a private letter is calculated using a sample t test. The result of research when tested by using t test of one sample is the ability to write a personal letter equal to the value of comparison. The comparative value applied in this study was 68% of the maximum score. The writing ability of students is equal to the value of comparison. The meaning of the ability to write personal letters of class VIII students MTs As-Syafi'iyyah Air Panas Village Pendalian IV Koto Districts relatively low. In other words the hypothesis is accepted. Then tested using independent sample t test to know the differing ability of personal letter writing according to the sample group. The result is no difference in the ability to write personal letters of class VIII students according to the sample groups. In other words the second hypothesis is accepted. Overall, it can be concluded that the ability to write personal letters of grade VIII students MTs As-Syafi'iyyah Air Panas Village Pendalian IV Koto Districts relatively low, and there is no difference in the ability to write personal letters according to the sample group.Keywords: Ability, Writing, Private Letter, Student